Aspek-Aspek Pengelolaan dan Kepemimpinan Inovatif untuk Implementasi Teknologi Informasi dan Komunikasi di Perguruan Tinggi - Harjanto Prabowo (Binus Business Review, 2012)
The development of information and communication technology (ICT) quickly brings both challenges and opportunities for universities to the implementation, for administration and supporting activities as well; and is also used for activities in universities’ tridharma. This paper describes the management aspects of ICT in higher education and the importance of innovative leadership in succeeding the implementation of ICT in highereducation.